Impact of Malocclusion on Oral Health Related Quality of Life in Young People (Medical Forum Monthly, 2021)
Objective: To evaluate the self-assessment dental look pleasure among youngsters.Study Design: Questionnaire based descriptive cross-sectional study.Place and Duration of Study: This study was conducted at the Department of Orthodontics at Bacha Khan College of Dentistry Mardan from 15th July 2021 to 18th October 2021.Materials and Methods: This study was conducted on patients in aged 15 to 25 years who wants orthodontic treatment. Data was analyzed using SPSS-22. Mean±SD, frequencies, and percentages were calculated. Chi-square and t-tests were applied as per necessity of data, and p≤0.05 was measured as significant.Results: A total 217 (72.3%) sample size had good psychological well-being regarding their dental aesthetic appearance whereas 60 (20%) had satisfactory and 23 (7.7%) had poor psychological well-being regarding their dental appearance respectively.Conclusion: More than half of the total sample voiced desire with their dental aesthetic. Male patients were more pleased as compared to female patients, which is obviously due to the nature, thinking and misconception of our society that only those will have groom/bride who have beautiful looks.